HUBUNGAN STIMULASI IBU DENGAN PERKEMBANGAN MOTORIK PADA ANAK USIA 3-5 TAHUN DI PENDIDIKAN ANAK USIA DINI - Suyanti Suwardi (JKM (Jurnal Kebidanan Malahayati), 2021)
Background: According to WHO 2018, the problem of child development is increasing, the incidence rate in the United States ranges from 12-16%, Argentina 20%, Thailand 37.1%, and in Indonesia between 13-18%. Looking at the epidemiological data, it is necessary early detection and intervention in children with developmental disorders. Aceh Profile data in 2019 the percentage of health service coverage for children under five years of age has a effect, namely that 65% of the health of children under five must be monitored to ensure that their health is always in optimal condition.The Purpose: Research to determine the relationship between maternal stimulation on motor development in children aged 3-5 years in Paud INARA, Johan Pahlawan District, West Aceh Regency, 2020 ".Methods: The design of this study was a quantitative analytic survey using a cross sectional study. The total population was 36 respondents and the sample used a total population of 36 respondents. The data used are primary and secondary data. Data analysis using univariate and bivariate.Results: The results showed that the stimulation was good as many as 31 people and less good as many as 5, normal motor development as many as 30 people and not normal as many as 6 people, the relationship between maternal stimulation and motor development in children aged 3-5 years with p = 0.000 <0.05.Conclusion: in this study there is a relationship between maternal stimulation and motor development in children aged 3-5 years in PAUD Inara Kec. Johan Kab. West Aceh 2020. It is recommended for parents to stimulate children under five, and if you experience problems, immediately consult with health workers, especially midwives and pediatricians.Suggestion Health workers are expected to provide promotions about growth and development for parents so that parents know the good growth and development of children, so as to prevent child development problems as early as possible. Keywords: Stimulation, motor development, toddlers ABSTRAK Latar belakang: Menurut WHO 2018 bahwa masalah perkembangan anak semakin meningkat, angka kejadian di Amerika Serikat berkisar 12-16%, Argentina 20%, Thailand 37,1%, dan di Indonesia antara 13-18%, Melihat data epidemiologi tersebut, maka diperlukan deteksi dan intervensi dini pada anak dengan gangguan perkembangan. Data Profil Aceh tahun 2019 persentase cakupan pelayanan kesehatan anak balita lima tahun terakhir berflutuaksi yaitu 65% kesehatan balita harus dipantau untuk memastikan kesehatan mereka selalu dalam kondisi optimal.Tujuan: Penelitan untuk mengetahui hubungan stimulasi ibu terhadap perkembangan motorik pada anak usia 3-5 tahun di Paud INARA Kecamatan Johan Pahlawan Kabupaten Aceh Barat Tahun 2020”.Metode:Desain penelitian ini adalah survei analitik kuantitatif dengan menggunakan cross sectional study. Jumlah populasi sebanyak 36 responden dan sampel menggunakan total populasi yaitu sebanyak 36 responden. Data yang digunakan dengan menggunakan data primer dan sekunder. Analisa data menggunakan univariat dan bivariat.Hasil :Hasil penelitian diperoleh bahwa stimulasi baik sebanyak 31 orang dan  Kurang Baik  sebanyak 5, perkembangan motorik normal sebanyak 30 orang dan tidak normal sebanyak 6 orang, hubungan stimulasi ibu dengan perkembangan motorik pada anak usia 3-5 tahun dengan p= 0.000<0.05.Kesimpulan: dalam penelitian ini ada hubungan stimulasi ibu dengan perkembangan motorik pada anak usia 3-5 Tahun di PAUD Inara Kec. Johan Kab. Aceh Barat Tahun 2020. Disarankan bagi orang tua untuk melakukan stimulasi kepada anak balita, dan jika mengalami msalah segera berkonsultasi ke tenaga kesehatan khusunya Bidan dan dokter anak.Saran Bagi Petugas kesehatan diharapkan untuk memberikan promosi tentang tumbuh kembang bagi orang tua agar orang tua mngetahui tumbuh kembang anak yang baik, sehingga dapat mencegah masalah tumbuh kembang anak sedini mungkin. Kata Kunci : Stimulasi, perkembangan motorik, anak Balita